MPSSS impairs the immunosuppressive function of cancer-associated fibroblasts via the TLR4-NF-κB pathway - Xu, Yuwei (Biosci Rep, 2019)
The polysaccharides MPSSS was extracted from Lentinus edodes and has been reported to effectively inhibit tumor growth and eliminate the function of myeloid-derived immune suppressor cell-mediated T cell inhibition, thus improving the efficacy of cancer therapy. The exploration of how MPSSS affects the functions of cancer-associated fibroblasts (CAFs) will provide a new perspective for understanding the antitumor effects of MPSSS. In the present study, prostate CAFs were selected as target cells to study whether MPSSS affected cell proliferation and function. The results showed that MPSSS did not directly inhibit the growth of prostate CAFs but interfered with CAF-mediated T cell inhibition and affected the immunosuppressive function of prostate CAFs. Mechanistic studies were further performed and showed that MPSSS activated key node proteins in the NF-κB pathway that were dependent on MyD88, and a TLR4 inhibitor blocked the changes in these proteins and the effect of MPSSS. We hypothesize that MPSSS can activate the MyD88-dependent TLR4-NF-κB signaling pathway to change the function of CAFs. In conclusion, these results demonstrate that MPSSS can not only effectively inhibit the growth of prostate cancer as we previously reported but also alter the function of prostate CAFs by activating the TLR4-NF-κB pathway, providing a new strategy for the comprehensive treatment of tumors.